On the meaning and measurement of redistribution in cross-country comparisons - Peter J. Lambert; Runa Nesbakken; Thor O. Thoresen (Luxembourg Income Study (LIS), 2010)
There is confusion in the literature concerning the relationship between income inequality and redistribution in a cross-country perspective. The reason for this is that different contributions in the literature are not referring to the same characteristic. This is shown by addressing information about redistribution in an international context from a number of angles: the size measures, such as tax revenue and government spending, the progressivity and redistributive effect with which the size is financed on the tax side, and the redistributional effects of government spending. By employing micro data from the Luxembourg Income Study database in combination with more aggregated information from the OECD for 15 countries, we show that the answer to the question 'does more income inequality generate more redistribution?' depends on how the concept of redistribution is operationalized. Moreover, we argue that closer attention should be given to the common-base version of redistribution, which uses the 'transplant-and-compare' procedure of Dardanoni and Lambert (2002). This conceptualization of redistribution is in fact what many authors actually may have in mind when discussing the relationship between income inequality and redistribution.
Keywords: H11; H23; H53; 330; Redistributive effect; Personal income tax; Cross-country comparison; Einkommensverteilung; Einkommensumverteilung; Einkommensteuer; OECD-Staaten